Effect of repeated microwave disinfection on the surface hardness of a heat-cured denture base resin: An In vitro study - Priti Jaiswal; Neelam Pande; Rajlakshmi Banerjee; Usha Radke (Wolters Kluwer Medknow Publications, 2018)
Statement of the Problem: Disinfection of complete dentures is very crucial to prevent cross-contamination and infection. Microwave disinfection is a quick, easy, and effective means to disinfect dentures. However, the effect of repeated microwave cycles on the surface hardness property of heat-cured polymethyl methacrylate (PMMA) resin is not known. Materials and Methods: A total of 60 samples of heat-cured PMMA resin were fabricated for surface hardness. Each group was divided into four groups, according to the number of microwave cycles (MWC) applied for disinfection: control group (no disinfection) 0MWC, 1MWC group, 3MWC group, and 5MWC group. Results: No significant change on the surface hardness of a heat-cured denture base resin on repeated microwave disinfection. Conclusion: The repeated microwave disinfection showed statistically nonsignificant change on the surface hardness of the PMMA resin. Microwave disinfection can be safely used in regular practice to avoid cross-contamination and can also be suggested to patients for the regular denture hygiene.